The Role of Glucosinolates from Cruciferous Vegetables (Brassicaceae) in Gastrointestinal Cancers: From Prevention to Therapeutics - Catarina Melim; Maria R. Lauro; Isabel M. Pires; Paulo J. Oliveira; Célia Cabral (MDPI AG, 2022)
The gastrointestinal (GI) tract is composed of rapidly renewing cells, which increase the likelihood of cancer. Colorectal cancer is one of the most frequently diagnosed GI cancers and currently stands in second place regarding cancer-related mortality. Unfortunately, the treatment of GI is limited, and few developments have occurred in the field over the years. With this in mind, new therapeutic strategies involving biologically active phytocompounds are being evaluated as anti-cancer agents. Vegetables such as broccoli, brussels sprouts, cabbage, cauliflower, and radish, all belonging to the Brassicaceae family, are high in dietary fibre, minerals, vitamins, carotenoids, polyphenols, and glucosinolates. The latter compound is a secondary metabolite characteristic of this family and, when biologically active, has demonstrated anti-cancer properties. This article reviews the literature regarding the potential of Cruciferous vegetables in the prevention and/or treatment of GI cancers and the relevance of appropriate compound formulations for improving the stability and bioaccessibility of the major Cruciferous compounds, with a particular focus on glucosinolates.